Practical Guidance on Biosimilars, With a Focus on Latin America: What Do Rheumatologists Need to Know?. Issue 2 (March 2019) - Azevedo, Valderilio Feijó; Babini, Alejandra; Caballero-Uribe, Carlo V.; Castañeda-Hernández, Gilberto; Borlenghi, Cecilia; Jones, Heather E.
Abstract : Background/Historical Perspective: Availability of biologic disease-modifying antirheumatic drugs (bDMARDs) has improved clinical outcomes in rheumatoid arthritis, but it also increased the cost of treatment. Biosimilars, the regulated copies of biologic products, have a potential to reduce health care costs and expand access to treatment. However, because of a complex development process, biosimilars can be considered only those noninnovator biologics with satisfactory supporting evidence (ranging from structural to clinical), as outlined in the recommendations by the World Health Organization (WHO). In Latin America, a heterogeneous regulatory landscape and nonconsistent approval practices for biosimilars create decision-making challenges for practicing rheumatologists. Summary of Literature: Most Latin American countries either have adopted or are in the process of adopting guidelines for the approval of biosimilars. However, among several marketed bDMARDs in the region, currently there are only 2 products that could be considered true biosimilars, based on the WHO criteria. The rest can be considered only intended copies, whose safety and efficacy are not fully established. One such product had to be withdrawn from the market because of safety concerns. Conclusions and Future Directions: Practicing rheumatologists in Latin America need to understand the regulatory situation for biosimilars in their countries. When considering bDMARDs that are not innovator products, clinicians should use only those that have been approved according to the WHO recommendations. For clarification, local health authorities or professional associations should be contacted.